In Situ Synthesis of B4C/TiB2 Composites from Low Cost Sugar Based Precursor - Cakir, E.; Ergun, C.; Sahin, F. C.; Erden, I. (TRANS TECH PUBLICATIONS LTD, 2010)
In the present study, a method based on sulfuric acid dehydration of sugar was developed to synthesis a precursor material, which can yield B4C/TiB2 composites at much lower temperatures compared to traditional carbothermal methods. The precursor material for pure B4C and B4C / TiB2 composites were heat treated at 1650 degrees C under Ar and Ar+H-2 atmosphere. Then the samples were characterized by X-ray diffraction (XRD) and crystallized B4C and B4C / TiB2 composites can be obtained at 1650 degrees C
Keywords: boron carbide; titanium diboride; ceramic synthesis; ceramic precursor; low temperature synthesis; MECHANICAL-PROPERTIES; TIB2; MICROSTRUCTURE; TIO2; Thermodynamics; Science & Technology - Other Topics; Physics